(6x-5)(8x+3)=0

Simple and best practice solution for (6x-5)(8x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x-5)(8x+3)=0 equation:


Simplifying
(6x + -5)(8x + 3) = 0

Reorder the terms:
(-5 + 6x)(8x + 3) = 0

Reorder the terms:
(-5 + 6x)(3 + 8x) = 0

Multiply (-5 + 6x) * (3 + 8x)
(-5(3 + 8x) + 6x * (3 + 8x)) = 0
((3 * -5 + 8x * -5) + 6x * (3 + 8x)) = 0
((-15 + -40x) + 6x * (3 + 8x)) = 0
(-15 + -40x + (3 * 6x + 8x * 6x)) = 0
(-15 + -40x + (18x + 48x2)) = 0

Combine like terms: -40x + 18x = -22x
(-15 + -22x + 48x2) = 0

Solving
-15 + -22x + 48x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-3 + -8x)(5 + -6x) = 0

Subproblem 1

Set the factor '(-3 + -8x)' equal to zero and attempt to solve: Simplifying -3 + -8x = 0 Solving -3 + -8x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -8x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -8x = 0 + 3 -8x = 0 + 3 Combine like terms: 0 + 3 = 3 -8x = 3 Divide each side by '-8'. x = -0.375 Simplifying x = -0.375

Subproblem 2

Set the factor '(5 + -6x)' equal to zero and attempt to solve: Simplifying 5 + -6x = 0 Solving 5 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -6x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = 0 + -5 -6x = 0 + -5 Combine like terms: 0 + -5 = -5 -6x = -5 Divide each side by '-6'. x = 0.8333333333 Simplifying x = 0.8333333333

Solution

x = {-0.375, 0.8333333333}

See similar equations:

| 187=-x+8 | | x+.05x=456 | | x+.05x=110 | | f(x)=x^3-6x^2-x+6 | | p^6-1=0 | | Y=-14x*-70x | | 2x/11 | | 3x+6x+2=-4x | | 10+10x=50+2x | | 8+w-4.7w-.5= | | 15x^2+26x+7= | | 125x^6-8=equation | | -4/9x=8 | | 5/√5xy^2 | | 5/√(5xy^2 | | 0=x^2+x-8 | | 80p^2r-245b^2r=0 | | 2v^2-10+12=0 | | 16v^4y^5-4v/4v^3x^6 | | 2r=7(r-15) | | 6m+3(2m-1)=-27 | | 5lnx-4=7 | | -9+20x=16 | | 5=-10n | | r=7r-52.5 | | 3a-(2-9b)= | | 50/950 | | 2m+(9m^2+3m)= | | 3x-17=-17+9x | | 7y-24=-15+6y | | 24y+2x=114 | | 4*x-1=X-2 |

Equations solver categories